Analyzing the Effects of a 12-Week Yoga and Elastic-Band Resistance Training Program on Functional Fitness in Intermediate-Level Male Tennis Athletes: A Randomised Controlled Trial - Choudhary, Prashant Kumar; Choudhary, Suchishrava; Wulandari, Indri; Saha, Sohom (Physical Education Theory and Methodology, 2025)
Background. Yoga and elastic-band resistance training (EBRT) are cost-effective methods to enhance physical function, yet their combined effects on competitive young tennis athletes remain underexplored. Objectives. This study aimed to examine the impact of a 12-week yoga + EBRT program on functional fitness in intermediate-level male tennis players. Materials and Methods. Thirty-four athletes (age 20.3 ± 1.5 years) were randomly assigned to an experimental group (yoga + EBRT, n = 17) or control group (regular tennis training, n = 17). Functional outcomes were assessed at baseline, week 6, and week 12 using the Chair Stand, Arm Curl, Chair Sit-and-Reach, Single-Leg Stance, and Timed Up-and-Go (TUG) tests. A 2 × 3 repeated-measures ANOVA evaluated group × time effects, with effect sizes reported as Cohen’s d and partial eta squared (η²p) with 95% confidence intervals (CIs). Results. Significant group × time interactions were found for all outcomes (p < 0.01). At post-test, the experimental group showed superior performance compared with controls in arm curl (+4.2 reps, 95% CI [1.77, 6.63], d = 1.16), chair stand (+2.3 reps, 95% CI [−0.23, 4.83], d = 0.61), sit-and-reach (+6.2 cm, 95% CI [3.12, 9.28], d = 1.35), and TUG (−1.0 s, 95% CI [−1.44, −0.56], d = −1.53). Improvements in single-leg stance were small and non-significant (+1.2 s, 95% CI [−2.03, 4.43], d = 0.25). Attendance averaged 88%, with no adverse events reported. Conclusions. A 12-week yoga and EBRT program significantly improved muscular endurance, flexibility, and mobility compared with regular training, with large effect sizes observed for upper-body endurance, flexibility, and dynamic agility. These findings support the use of combined yoga and elastic-band protocols as a practical conditioning option for young tennis athletes. Further studies should integrate tennis-specific performance metrics to confirm sport transferability.